GRADUAL FLOWERING AND FRUITING TECHNOLOGY (“BUJANGSETA”) THROUGH FERTILIZER MANAGEMENT IN SIAM (Citrus nobilis L.) CV. PONTIANAK - A., Sugiyatno; Devy, Nirmala F; ., Hardiyanto; ., Harwanto; Dwiastuti, Mutia E (Emirates Journal of Food and Agriculture, 2021)
Fruit bearing of citrus species such Tangerine or Siam cv. Pontianak caused fruit yield and quality variation. Research was carried out in Banaran Experimental Garden under Indonesia Citrus and Subtropical Fruit Research Institute, Batu, East Java Indonesia, from November 2019 to September 2020. The objective of this study was to evaluate Bujangseta (BS) technology on the growth, physiology, flowering, and yields of Siam cv. Pontianak. 158 trees of 7-year-old 'Pontianak' Siam (Citrus nobilis L.) cultivar were divided into two blocks in which each block has been subjected to Bujangseta technology, and control, respectively. T Test was used to evaluate two treatments. The results showed that BS technology induced the leaf area, leaf pigments, fruit set, and total fruits/plant, whereas starch and sugar content of leaves decreased. Fruit harvesting on the BS and control (C) treatments during the period of January to August 2020 had been done 4 and 2 times, respectively. The total fruit weight/tree treated with BS significantly increased by 112% compared to C. The BS’s fruits quality such as size, juice volume and total soluble solid were significantly better than control. Improvement of fertilizer application is recommended to improve the ‘Bujangseta’ technology in order to increase the gradual flowering and fruiting in Siam group throughout the year. Keywords: Bujangseta, Citrus nobilis L, fertilizer, Siam cv. Pontianak, Tangerine